The food of Mallard ducklings in a wet gravel quarry, and its relation to duckling survival - Street, Michael (Wildfowl, 1977)
This paper describes the food found in Mallard Anas platyrhynchos ducklings in the gravel pit study area at Great Linford, Buckinghamshire, and relates the unusually high duckling mortality, estimated to be at least 77%, to the relatively low consumption of insect foods by the downy ducklings. The emergence of insects in the breeding reserve was monitored and the duckling mortality was observed to be greatest before the peak of insect emergence in June. It is suggested that the low consumption of essential invertebrate foods is a result of the reduced availability of such foods because of the low productivity of the man made, ecologically immature newly flooded gravel pit habitat.